Art and Archaeology. (25th March 2015) - Unknown
Abstract : The archaeologist Heinrich Schliemann once met, in London, the poet Alfred Tennyson – who, though he saluted Mount Ida tenderly, never travelled much south of the Dolomites. In the course of conversation, Schliemann remarked: 'Hissarlik, the ancient Troy, is no bigger than the courtyard of Burlington House'. 'I can never believe that', Tennyson replied. Most of us, I dare say, would understand Tennyson's disbelief – and agree, accordingly, with the sentiment that Troy the site is not a marvellous 'visitor experience'. The location may be broadly evocative – for those imaginatively predisposed to survey a landscape of epic combat. Yet the excavated remains are rather underwhelming, and difficult to comprehend. The huge trench cut through the Bronze Age settlement by Schliemann, and the resultant spoil heap left on the northern edge of the citadel, certainly contribute to a sense of confusion. But that aside, the multiple layers of habitation, from c. 3000bc until Byzantine times, customarily represented like a pile of pancakes in archaeological diagrams, will test even those pilgrims arriving with some expertise in ancient construction methods. Choice finds from the city are lodged in remote museums; and the substantial extent of Troy in Hellenistic, Roman, and possibly earlier times, indicated mainly by geophysical prospection, is hardly discernible. So archaeologists, post-Schliemann, have to work hard to make the 'Trojan stones speak' – at least if they also wish to avoid the charge of being obsessed (as Schliemann notoriously was) with establishing some kind of historical reality for Homer's epic. The late Manfred Korfmann, director of the international excavations at Troy since 1988, produced an enthusiastic guidebook. Now his colleague C. B. Rose has made a one-volume synthesis of the results so far, The Archaeology of Greek and Roman Troy . This will be particularly welcome for students unable or unwilling to access the annual excavation journal, Studia Troica . But novices, I fear, may soon despair of grasping the phases of stratification and ceramic assemblage more often cited by the author than explained (e.g. 'LH III2a/VIh'). And any reader seeking new answers for old questions about the site's relationship to 'the Trojan War' should prepare for disappointment. Much of the evidence for Troy in the late Bronze Age – the period of c. 1250bc, generally reckoned to correlate with events transformed into epic – remains elusive: where, for example, are graves comparable to those of Mycenae? On the other hand, the lesson of the multi-period approach is that Troy the historical city largely constructs its identity upon Troy the mythical citadel – as does the Troad region. So Rose does well to devote an entire chapter to the remarkable archaic sarcophagus recovered in 1994 from a tumulus in the Granicus valley, with scenes of the sacrifice of Polyxena, Hecuba's attendant distress, and some kind of celebration. The iconography here may not be easy to relate to the gender of the deceased (a middle-aged man, according to osteological analysis). Yet it makes a visual statement about the sort of mythical bloodline to be claimed in the region: and, in due time (for Rose's survey is chronological), we will see the epigraphic and monumental evidence for similar ancestral claims by members of the Julio-Claudian clan.